PENGARUH PROGRAM CLEANLINESS, HEALTH, SAFETY, ENVIRONMENT (CHSE) TERHADAP KEPUASAN DAN NIAT BERKUNJUNG KEMBALI KE DAYA TARIK WISATA TANAH LOT TABANAN BALI - Putu Cahaya Semesta; I Wayan Suardana; I Nyoman Ariana (Jurnal Belantara, 2023)
The tourism industry has experienced a decline due to the Covid-19 pandemic. The Indonesia Central Statistics (BPS) noted that the number of foreign tourist arrivals to Indonesia between January and November 2020 was only 3.89 million. In line with the implementation of the health protocol, the Ministry of Tourism and Creative Economy in 2020 issued a guide book and certification program for the implementation of Cleanliness, Healthy, Safety and Environment (CHSE) in the tourism sector. On September 25, 2020 Tanah Lot already pocketed the CHSE certificate. This study was designed to assess the relationship between the implementation of the CHSE program on satisfaction and revisit intention of tourists visiting the Tanah Lot Tourist Attraction, Tabanan. This study uses quantitative methods. The sample in this study was 30-100 samples using accidental sampling technique. The data collection technique in this study was done by distributing online and offline to visitors visiting Tanah Lot. Data analysis in this study used two analytical techniques, namely Structural Equation Modeling - Partial Least Square (SEM-PLS) and descriptive qualitative analysis. The results of this study indicate that CHSE, both directly and through mediation, has a positive and significant effect on the satisfaction and intention to revisit visitors who travel to Tanah Lot. Satisfaction has a positive and significant effect on the intention to revisit tourists who travel to Tanah Lot.